2020
DOI: 10.3390/ijms21124289
|View full text |Cite
|
Sign up to set email alerts
|

Brain Overexpression of Uncoupling Protein-2 (UCP2) Delays Renal Damage and Stroke Occurrence in Stroke-Prone Spontaneously Hypertensive Rats

Abstract: The downregulation of uncoupling protein-2 (UCP2) is associated with increased brain and kidney injury in stroke-prone spontaneously hypertensive rats (SHRSP) fed with a Japanese style hypersodic diet (JD). Systemic overexpression of UCP2 reduces organ damage in JD-fed SHRSP. We examined the effect of brain-specific UCP2 overexpression on blood pressure (BP), stroke occurrence and kidney damage in JD-fed SHRSP. Rats received a single i.c.v. injection of a lentiviral vector encoding UCP2 (LV-UCP2), or an empty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…We also showed that GJW and GJE increase the expression of UCP2, which is a component of another mitochondrial ROS-associated signaling pathway [42][43][44]. Located in the inner mitochondrial membrane, UCP2 functions to protect against oxidative stress by regulating the production of superoxide anions [42,[44][45][46]. Our findings illustrated that GJW and GJE reduce mitochondrial ROS via the upregulation of UCP2, not by regulating antioxidant enzymes per se.…”
Section: Discussionmentioning
confidence: 52%
“…We also showed that GJW and GJE increase the expression of UCP2, which is a component of another mitochondrial ROS-associated signaling pathway [42][43][44]. Located in the inner mitochondrial membrane, UCP2 functions to protect against oxidative stress by regulating the production of superoxide anions [42,[44][45][46]. Our findings illustrated that GJW and GJE reduce mitochondrial ROS via the upregulation of UCP2, not by regulating antioxidant enzymes per se.…”
Section: Discussionmentioning
confidence: 52%
“…Research on HEK293 and HeLa cells has found that the inhibition of Drp1-induced fission impaired the selectivity of mitophagy, thus enhancing its rate of elimination of even healthy mitochondria via the unchecked PINK1/Parkin pathway (Burman et al, 2017). After selective overexpression of uncoupling protein-2 (UCP2) in the corpus striatum of stroke-prone spontaneously hypertensive (SHRSP) rats, Busceti et al (2020) found the upregulation of OPA1 and Fis1, which respectively amplified mitochondrial fusion and fission in the striatum tissue. Although the causality was not explicit, this experiment implied that UCP2 exerted neuroprotection by driving mitochondrial fusion and fission.…”
Section: Fission Acts As a Neuroprotective Factormentioning
confidence: 99%
“…In this work, we analyzed all the publicly available independent experimental RNA-Seq datasets-on transcriptomes from the tissues of hypertensive versus normotensive patients [26][27][28][29][30][31][32][33][34][35][36][37][38][39], hypertensive versus normotensive animals [7,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57], and domestic versus wild animals [72,[176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193].…”
Section: Degs Under Studymentioning
confidence: 99%